Pemberdayaan Masyarakat Pengelolaan Sampah Plastik Melalui Sosialisasi dan Pelatihan Pemanfaatan Sampah Plastik Menjadi Paving Block - Wahidah, Syifa Nurlaeli; Lubis , Adella Silvany; Asyi Zamilah, Apipah Rohadatul; Syaida Rahman , Malwa Aulia; Rosidi Alfariza , Mochamad Nizar; Arfad , Muhammad Ziyan; Pulungan , Syalsabila; Muharry, Andy (CV. Era Digital Nusantara, 2025)
Waste management is a serious issue in various regions of Indonesia, including in Nagrog Village, RT 01 RW 08, Sukamenak Village, Tasikmalaya City. This activity aims to increase community awareness and skills in managing plastic waste using counseling methods and training in making paving blocks. Through the Participatory Rural Appraisal (PRA) method, the community is actively involved, starting from counseling to the practice of making paving blocks. The results of the activity show that the community is able to understand the concept of waste management and is successful in producing paving blocks that have economic value. This program creates a community-based empowerment model that has potential for sustainability.